OPTIMALISASI PEMANFAATAN SUMBER DAYA HAYATI RAMBUTAN KELENGKENG DESA KARANGREJO, BOROBUDUR KABUPATEN MAGELANG MELALUI OKULASI - Nugraheni Widyawati; Lasmono Tri Sunaryanto; Djoko Murdono (Agric, 2016)
ABSTRACTKarangrejo village, subdistrict of Borobudur, Magelang regency has Punthuk Setumbu as a very beautiful place to watch the sunrise from the peak of Mounts Merapi and Merbabu with Borobudur shadow in the foreground. Beside its famous sunrise view, Karangrejo also famous with its rambutan fruit with trees nearly at every home yard. From pre-findings activities, there was a certain good rambutan variety that they called “rambutan klengkeng” or longan rambutan. This special kind of rambutan is so sweet, with thick flesh, easy to peel and fresh longer. It has potential to develop it as “Rambutan Karangrejo” as a special local type that become identity and source of income of Karangrejo villagers. The main objective of this activity are: (1) to identify the potentiallity of longan rambutan superior characteristics; (2) to improve the ability of farmers group to multiply the longan rambutan trees through grafting techniques. The method used were survey, focus group discussions, training, demonstration, self practicing and mentoring. The results are: 1. Some fruits that potential to develop are include rambutan, banana and jackfruit. Longan Rambutan fruit have many good characteristics such as its taste, thickness of flesh fruit, flavor, easy to peel and fresh longer. 2. The training for grafting technique have improved the understanding and skills of farmers group in terms of preparing rootstock, eye patch, prepare materials and tools, performing grafting techniques, monitoring and caring the grafting tress.